The study on strategic planning process and performance of Universiti Malaysia Perlis - Siti Farah Syazana, Mohamed Yusoff (2015)
This research aims to identify strategic planning process characteristics in Universiti Malaysia Perlis (UniMAP) and to examine its relationship with firm performance. Existing literature, both theoretical and empirical, is examined to identify the state of knowledge regarding strategic planning process. This study was done via a survey of Universiti Malaysia Perlis (UniMAP) staf who involves in strategic planning process. The results of the survey provided information on the relationship of strategic planning process applied in UniMAP and how it reflects towards the firm performance. Key findings provided empirical evidence about the involvement of top and line management in planning, and the impact of strategic planning process towards UniMAP performance. Furthermore, the study found a strong positive relationship between strategic planning and firm performance. This research gives new empirical evidence about the value of strategic planning to corporate performance in the context of UniMAP